Saliva as a tool for monitoring hemodialysis: a systematic review and meta-analysis - Renata Prata Cunha Bernardes RODRIGUES; Walbert de Andrade VIEIRA; Walter Luiz SIQUEIRA; Bernardo Antonio AGOSTINI; Eduardo Buozi MOFFA; Luiz Renato PARANHOS (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract This study aimed to assess whether the reductions in serum urea and creatinine levels are different from the reductions in salivary urea and creatinine levels that occur after hemodialysis in chronic renal patients. The systematic review protocol was registered in the PROSPERO database. Eight databases were searched to identify pretest-posttest studies of chronic kidney disease patients undergoing hemodialysis, with no language or year restrictions. The JBI Critical Appraisal Tool was used to assess the risk of bias. Meta-analyses using random-effect models were conducted to compare salivary and serum correlations and to pooled mean and proportion differences from pre- to posthemodialysis urea and creatinine levels by subgroup analysis. The I2 test was used to assess heterogeneity, and a meta-regression was performed to statistically assess correlations and differences in the pooled effects pre- and postdialysis. The Grading of Recommendation, Assessment, Development, and Evaluation (GRADE) was used to assess the certainty of evidence. The search resulted in 1404 records, and only six studies (n = 252 participants) fulfilled the eligibility criteria and were included. The studies were published between 2013 and 2018. All studies showed a significant reduction in both salivary and serum urea/creatinine levels. All eligible studies presented a low risk of bias. The meta-analysis shows a moderate to high correlation between salivary and blood levels of urea (r: 0.79; 95% CI: 0.56-1.00) and creatinine (r: 0.64; 95%CI: 0.16-1.00), with a very low level of certainty. The reductions in salivary urea and creatinine levels are similar to and correlated with the reductions in blood urea and creatine levels after hemodialysis among chronic kidney disease patients.